Low frequency noise in the unstable contact region of Au-to-Au microcontact for microelectromechanical system switches - Qiu, Haodong (2016)
The noise behavior of Au-to-Au microcontact for microelectromechanical system switches has been experimentally studied in the unstable contact region. The results suggest that the electrical conduction remains nonmetallic at the initial stage during contact formation due to the existence of alien films, and traps in the alien layer located at the contact interface could play an important role in determining the conduction noise. The conduction fluctuation induced by electron trapping-detrapping associated with the hydrocarbon layer is found to be an intrinsic noise source contributing to the low frequency noise in the unstable contact region.